2000
DOI: 10.1038/sj.ijo.0801244
|View full text |Cite
|
Sign up to set email alerts
|

Genomic structure and mutations in adipose-specific gene, adiponectin

Abstract: BACKGROUND: Adiponectin is a collagen-like plasma protein speci®cally synthesized in adipose tissue. Plasma adiponectin concentrations are decreased in obesity whereas it is adipose-speci®c. OBJECTIVE: To clarify the signi®cance of the genetic variations in adiponectin gene on its plasma concentrations and obesity. SUBJECTS: Two hundred and nineteen unrelated adult Japanese subjects (123 men and 96 women, age: 20 ± 83 y, BMI: 16 ± 43 kgam 2 ) including 77 obese subjects (BMI b 26.4 kgam 2 ). MEASUREMENT: Human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
215
1
22

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 350 publications
(246 citation statements)
references
References 37 publications
8
215
1
22
Order By: Relevance
“…Similar results were obtained in other studies in other ethnic groups with regard to associations of rare -11377G (9,18,36, 47,50), or -11391G>A (51) allele/genotype/haplotype carriers with obesity and obesityrelated phenotypes. In contrast, some other studies demonstrated that the common -11377C allele was strongly associated with obesity and MetS parameters (17,52). Our findings are also consistent with previous reports in different populations and different age groups (53,54,55) stating that ADIPOQ gene may play an important role in MetS.…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were obtained in other studies in other ethnic groups with regard to associations of rare -11377G (9,18,36, 47,50), or -11391G>A (51) allele/genotype/haplotype carriers with obesity and obesityrelated phenotypes. In contrast, some other studies demonstrated that the common -11377C allele was strongly associated with obesity and MetS parameters (17,52). Our findings are also consistent with previous reports in different populations and different age groups (53,54,55) stating that ADIPOQ gene may play an important role in MetS.…”
Section: Discussionsupporting
confidence: 92%
“…Nonsynonymous amino acid substitutions may contribute to the variation of circulating adiponectin by affecting the spatial organization of the protein and interfering with posttranscriptional modification, multimerization or interaction of the protein with its receptors (16). Variants including G84R, G90S, H111Y and R112C have been reported to be associated with adiponectin level and suggested to be functionally relevant (16,33,34). However, these variants were rare in initial studies (MAF,0.02) and are not included as HapMap or 1000 Genomes Project Pilot imputed SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…Differentiated adipocytes can function in an endocrine manner to secrete several cytokines, called ''adipokines,'' which include TNF-a, IL-6, leptin, adiponectin, and others (Spiegelman and Flier 1996;Matsuzawa et al 1999). These genes are found to contain binding sites for TFAP2 in their promoter (Kroeger and Abraham 1996;Isse et al 1995;Takahashi et al 2000). Given such observations, we suggest that TFAP2B plays a key role in the pathogenesis of type 2 A d ip o c y t e B r a in H e a r t K id n e y L iv e r L u n g P a n c r e a s P la c e n t a S k e le t a l m u s c le T h y m u s F e t a l B r a in F e t a l k id n e y F e t a l lu n g A d ip o c y t e B r a in H e a r t K id n e y L iv e r L u n g P la c e n t a S k e le t a l m u s c le ND P a n c r e a s Fig.…”
Section: Discussionmentioning
confidence: 99%